An investigation of the ABA laser cladding process: A new Laser – Direct Energy Deposition (DED) technique - Koti, Daniel (2024)
Blown powder directed energy deposition (DED), commonly known as laser metal deposition (LMD), is discussed in this thesis. All industries demand engineering components with required surface characteristics, including suitable wear and corrosion resistance and hardness properties. Thus, in some cases high-grade alloys are essential to achieve the desired surface quality. However, industries are primarily interested in reducing the cost of engineering parts with these surface characteristics. With a cheaper substrate material and the appropriate coating alloy, cost reductions can be achieved very easily. High powder catchment efficiency, deposition rate and coverage rate can enhance productivity and increase cost-effectiveness. Laser cladding is an effective technique for changing the physical and chemical properties of material surfaces. This thesis starts by providing guidelines and advice for researchers and engineers in the field of laser cladding and related Direct Energy Deposition (DED) techniques, to help establish a standardised approach to quality assessment and productivity metrics. Factors considered are; deposit geometry, porosity, cracking, dilution, deposition rate/coverage rate and powder catchment efficiency. Although there is an exceptionally large body of research work on laser cladding and related Direct Energy Deposition (DED) techniques, there are no clear guidelines about which quality and productivity parameters are important to the relevant branches of industry, nor are there any general rules about what constitutes a high-quality deposit. The main focus of the work in this thesis concerns investigation of a new laser cladding technique (‘ABA’ cladding) wherein a series of separate, or only slightly overlapping clad tracks are laid down initially (the ‘A’ tracks), and these are later interleaved with tracks which can use different parameters (the ‘B’ tracks). ‘ABA’ cladding was found to have considerable benefits over traditional laser cladding including improved powder catchment efficiency and coverage rates, more predictable metallurgy, and dilution levels. The ‘ABA’ process was studied in order to understand the underlying reasons for the observed benefits. The majority of the study was conducted using high-speed video frames, in conjunction with cross-sectional and surface images of the clad and quantitative analysis of the results. Manufacturing companies could benefit from several of the results generated.